Improving Poetry writing ability Using Acrosstic techniques in Class VII Students of Banau National Junior High School Ternate City - Agus Hi Jamal (EDU Journal - English Department of UMMU Journal, 2022)
This study aims to describe learning used acrostic technique to improve the ability to write poetry at the seventh grade students of Banau Junior High School Ternat. The design of this research is classroom action research (CAR). Classroom Action Research (CAR) is a process that shows a continuous cycle of repeated activities. The main concept of action research by Kemmis and Mc Taggart consists of 4 (four) stages of the classroom action research process, namely 1) planning, 2) action, 3) observation, and 4) reflection. (Susetyo, 2010:97). The results of the research that has been carried out at the Banau National Junior High School in Ternate will be described in cycles carried out during the teaching and learning process in the classroom. The steps taken in this study consisted of planning, implementing actions, observing (observing), and reflecting. Learning research conducted in the teaching and learning process is carried out at the time of permission from the relevant parties. Based on the results of data analysis student learning outcomes have increased from cycle I to cycle II. Based on the results of research conducted in class VII Banau National Junior High School Ternate by using acrostic techniques to improve students' writing abilities.